Supply-side subsidies to improve food access and dietary outcomes: Evidence from the New Markets Tax Credit. (November 2018) - Freedman, Matthew; Kuhns, Annemarie
In an effort to improve diet and health outcomes, policymakers have increasingly turned to supply-side subsidies aimed at encouraging investment by supermarkets and other food retailers in low-income areas. This article examines whether the US federal government's New Markets Tax Credit (NMTC) has affected the entry of retail food establishments, and in turn food shopping and purchasing patterns, in low-income communities. To identify the impacts of the programme, we take advantage of a discontinuity in NMTC funding generated by the formula used to determine the eligibility of census tracts for investment under the programme. We find that the NMTC Program has had modest, but positive impacts on supermarket entry in low-income communities. Based on household-level scanner data, there are no detectable effects on households' food purchasing patterns in affected neighbourhoods, at least in the short run.